CHOROIDAL THICKNESS IN DIABETIC RETINOPATHY ASSESSED WITH SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY. Issue 1 (January 2018) - Laíns, Inês; Talcott, Katherine E.; Santos, Ana R.; Marques, João H.; Gil, Pedro; Gil, João; Figueira, João; Husain, Deeba; Kim, Ivana K.; Miller, Joan W.; Silva, Rufino; Miller, John B.
Abstract : Purpose: To compare the choroidal thickness (CT) of diabetic eyes (different stages of disease) with controls, using swept-source optical coherence tomography. Methods: A multicenter, prospective, cross-sectional study of diabetic and nondiabetic subjects using swept-source optical coherence tomography imaging. Choroidal thickness maps, according to the nine Early Treatment Diabetic Retinopathy Study (ETDRS) subfields, were obtained using automated software. Mean CT was calculated as the mean value within the ETDRS grid, and central CT as the mean in the central 1 mm. Diabetic eyes were divided into four groups: no diabetic retinopathy (No DR), nonproliferative DR (NPDR), NPDR with diabetic macular edema (NPDR + DME), and proliferative DR (PDR). Multilevel mixed linear models were performed for analyses. Results: The authors included 50 control and 160 diabetic eyes (n = 27 No DR, n = 51 NPDR, n = 61 NPDR + DME, and n = 21 PDR). Mean CT (ß = −42.9, P = 0.022) and central CT (ß = −50.2, P = 0.013) were statistically significantly thinner in PDR eyes compared with controls, even after adjusting for confounding factors. Controlling for age, DR eyes presented a significantly decreased central CT than diabetic eyes without retinopathy (β = −36.2, P = 0.009). Conclusion: Swept-source optical coherence tomography demonstrates a significant reduction of CT in PDR compared with controls. In the foveal region, the choroid appears to be thinner in DR eyes than in diabetic eyes without retinopathy. Abstract : This cross-sectional, multisite study explored the advantages of swept-source optical coherence tomography to compare the choroidal thickness of diabetic eyes with different stages of disease with nondiabetic controls. Previous studies with spectral domain optical coherence tomography were inconsistent. The results revealed that only eyes with proliferative disease presented a reduced choroidal thickness compared with controls.